The nature of PIS/COFINS and the Brazilian general insurance sector: a review of the nature of PIS/COFINS and their accounting treatment in the Brazilian general insurance sector - Araújo, Filipe Reis (2018)
The inconsistencies commonly found in the design of the Brazilian tax legislation and framework, allied to the specificities of the financial services industry, has led to very different approaches to the accounting treatment of PIS / COFINS. For instance, whilst some multinational banks and insurance companies with operations in Brazil have categorised and reported PIS / COFINS as income tax for IFRS purposes, Brazilian private insurance regulatory rules require PIS / COFINS to be accounted for as administrative expenses. An investigation of the nature of taxes on consumption and value-added taxes (VAT) has shown that PIS / COFINS are essentially taxes on consumption, which share the same economic base as IPI, ICMS and ISS. By comparing the Brazilian PIS / COFINS model with the Australian Goods and Services Tax (GST) model for general insurance (GI) companies, it becomes more evident that there are similarities in both approaches for estimating the value added in this financial services segment. Therefore, it becomes necessary to recognize in the Brazilian tax legislation the consumption nature of PIS /COFINS and this would not necessarily require very significant alterations to the way the current PIS / COFINS methodology operates for general insurers in Brazil. Nonetheless, accounting standards and practices as well as the regulatory framework should be adjusted to ensure that general insurance revenues would be recognised net of PIS / COFINS, resulting in a more consistent approach to the accounting treatment of PIS / COFINS by general insurance organizations in both Brazilian GAAP and IFRS. Treating the company's revenue without considering taxes and other values that will simply be passed on to the government increases the quality of the accounting information. A tax reform in Brazil is required to simplify not only the tax system but also to address some inadequate Brazilian accounting practices such as the consideration of some consumption taxes as part of the accounting revenue.